2011
DOI: 10.1007/s00024-011-0428-6
|View full text |Cite
|
Sign up to set email alerts
|

New Seismic and Tomography Data in the Southern Part of the Harghita Mountains (Romania, Southeastern Carpathians): Connection with Recent Volcanic Activity

Abstract: The southern part of the southeastern Carpathians represents the site of the most recent volcanic eruptions of the entire Carpathian-Pannonian region. The products of these eruptions range from 42 to 10 Ka radiocarbon ages in the South Harghita Mountains (high K calc-alkaline rocks with adakite-like features), and at 1.2-0.6 Ma K-Ar ages in the Perşani Mountains (alkali basalts). They were emplaced in a post-collisional regime. Ciomadul volcano is located at the southernmost part of the NW-SE oriented Cȃlimani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
(54 reference statements)
10
31
0
2
Order By: Relevance
“…Furthermore, the post volcanic activity transports significant amounts of CO 2 and other volatiles to the surface. These tectono-magmatic processes are also associated with high-intensity geothermal anomalies, micro-seismicity and teleseismic wave attenuation beneath the SE Carpathians volcanic area and the presence of a critical low-velocity crustal anomaly observed in high-resolution seismic tomography (Popa et al 2012). Since the study area is populated, the monitoring and, eventually, warning of these potential geological hazards (seismic and volcanic) are of prime importance.…”
Section: Why This Area?mentioning
confidence: 99%
“…Furthermore, the post volcanic activity transports significant amounts of CO 2 and other volatiles to the surface. These tectono-magmatic processes are also associated with high-intensity geothermal anomalies, micro-seismicity and teleseismic wave attenuation beneath the SE Carpathians volcanic area and the presence of a critical low-velocity crustal anomaly observed in high-resolution seismic tomography (Popa et al 2012). Since the study area is populated, the monitoring and, eventually, warning of these potential geological hazards (seismic and volcanic) are of prime importance.…”
Section: Why This Area?mentioning
confidence: 99%
“…Seismic tomography data support an active crustal magma chamber at depths of 8-20 km (Popa et al, 2012). However, to assess the possibility of future volcanic activity, a detailed chronology of the last eruptions is required.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The eruptive centres appear to be structurally controlled and show a rough NE-SW 190 trending alignment. Popa et al (2012) recorded subcrustal seismicity beneath the Perşani area 191 and, using seismic tomography modelling, suggested that a low-velocity anomaly could be 192 inferred at the crust-mantle boundary. The youngest basalt volcano (Putikov vŕšok; Šimon and 193 Halouzka, 1996) of the CPR is located near Banska Štiavnica upon the Late Pleistocene 194 terrace of the river Hron.…”
Section: (Stradner Kogel Klöch Steinberg) the Perşani Volcanic Fiementioning
confidence: 99%